2021
DOI: 10.1002/cctc.202100460
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Catalyst Design Heuristics from Random Catalyst Dataset and their Utilization in Catalyst Development for Oxidative Coupling of Methane

Abstract: In the oxidative coupling of methane (OCM), the activation of methane and the suppression of deep oxidation are in a persistent trade-off relationship, and a catalyst design strategy that balances the activity and the selectivity is desired. In this study, we analyzed a random catalyst dataset for OCM that was earlier obtained by high-throughput experimentation, and extracted heuristics such as elements, supports, and their combinations related to methane activation at a low temper-ature and selective formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 39 publications
(91 reference statements)
0
13
0
Order By: Relevance
“…It is particularly interesting that based on none/La 2 O 3 performance as a comparison standard the Ba and La impregnations induce positive features at C 2 yield, whereas Fa, Mn, and La are negative effects at C 2 yield. Preferred combination effects of Ba and La 2 O 3 have been described in earlier reports. , However, the best performance of 14.2% C 2 yield with 65.6% selectivity at 800 °C achieved Ba/La 2 O 3 does not satisfy the superior performance obtained over Mn-promoted three-element-supported La 2 O 3 , particularly LiFeBa-5Mn/La 2 O 3 . Accordingly, the synergetic effect mediates the novel OCM performance among Li, Fe, Ba, Mn, and La 2 O 3 .…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…It is particularly interesting that based on none/La 2 O 3 performance as a comparison standard the Ba and La impregnations induce positive features at C 2 yield, whereas Fa, Mn, and La are negative effects at C 2 yield. Preferred combination effects of Ba and La 2 O 3 have been described in earlier reports. , However, the best performance of 14.2% C 2 yield with 65.6% selectivity at 800 °C achieved Ba/La 2 O 3 does not satisfy the superior performance obtained over Mn-promoted three-element-supported La 2 O 3 , particularly LiFeBa-5Mn/La 2 O 3 . Accordingly, the synergetic effect mediates the novel OCM performance among Li, Fe, Ba, Mn, and La 2 O 3 .…”
Section: Resultsmentioning
confidence: 72%
“…Preferred combination effects of Ba and La 2 O 3 have been described in earlier reports. 41,42 However, the best performance of 14.2% C 2 yield with 65.6% selectivity at 800 °C achieved Ba/La 2 O 3 does not satisfy the superior performance obtained over Mn-promoted threeelement-supported La 2 O 3 , particularly LiFeBa-5Mn/La 2 O 3 . Accordingly, the synergetic effect mediates the novel OCM performance among Li, Fe, Ba, Mn, and La 2 O 3 .…”
Section: Resultsmentioning
confidence: 94%
“…77 In addition, several studies have recently reported data mining from the literature for the ML-assisted design and discovery of new heterogeneous catalysts for oxidative coupling of methane. [78][79][80][81][82][83] Fig. 3 shows the workow for the summary of a data mining sequence from the literature.…”
Section: Integration Of ML With Experimentsmentioning
confidence: 99%
“…Indeed, within the last a few years, the combined use of tailor-made experimental datasets obtained with a high throughput screening (HTS) machine and data analytic techniques such as multi-output ML and network profiling have presented new avenues for the design and elucidation of the nature and catalytic activity of catalysts, in particular OCM. [22][23][24][25][26][27][28][29][30][31][32] Several parallel reactor systems for effective data collection in a fixed bed catalytic reaction have become commercially available 33,34 and others have been proposed in the literature. 22,[35][36][37] Nevertheless, these systems still require special skills and entail high costs for operation and construction similar to the conventional modes of catalyst investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, within the last a few years, the combined use of tailor-made experimental datasets obtained with a high throughput screening (HTS) machine and data analytic techniques such as multi-output ML and network profiling have presented new avenues for the design and elucidation of the nature and catalytic activity of catalysts, in particular OCM. 22–32…”
Section: Introductionmentioning
confidence: 99%